![\begin{gathered} u(x)=x^2+7 \\ w(x)=\sqrt[]{x+8} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ldbqugmbv0qq75dujtxxn2px6n5mppw78w.png)
To find the value of the composed function (u ∘ w) evaluated in 1, we need to compose the functions.
![(u\circ w)=u(w(x))](https://img.qammunity.org/2023/formulas/mathematics/college/ta1h5yaankt0xw8azz5o38vdf2pxr8re05.png)
This means wherever we have x in the function u, we need to replace it with the expression for w(x) as follows:
![\begin{gathered} (u\circ w)=u(w(x))=w(x)^2+7 \\ \\ (u\circ w)=(\sqrt[]{x+8})^2+7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x31voucne1fhse97bsc5ubrnvv8n44si9g.png)
Solving the squared expression:
![\begin{gathered} (u\circ w)=x+8+7 \\ \\ (u\circ w)=x+15 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7b13badweqqzypw61mjykchc24x3fz5dad.png)
Now we know the composed function. We just need to evaluate it in x = 1, that is, replace 1 wherever the function has an x:
![\begin{gathered} (u\circ w)(1)=1+15 \\ \\ (u\circ w)(1)=16 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nckfdfi5isdt0y7hs4pl169hx326l2c1je.png)
Now we have the first answer: (u ∘ w)(1) = 16.
To find the value of (w ∘ u)(1) we follow the same logic:
![(w\circ u)=w(u(x))](https://img.qammunity.org/2023/formulas/mathematics/college/an99flj6izgzhf1tbn55q7rnbqc047x539.png)
In the function w, wherever we have an x, we replace it by the expression for u(x):
![\begin{gathered} (w\circ u)=w(u(x))=\sqrt[]{u(x)+8} \\ \\ (w\circ u)=\sqrt[]{(x^2+7)+8}=\sqrt[]{x^2+7+8} \\ \\ (w\circ u)=\sqrt[]{x^2+15} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1vyg8b7r0h72xev9r4nwz7qoraumlrszyw.png)
Now we know the composed function (w ∘ u). We just need to evaluate it in x = 1, that is, replace 1 wherever the function has an x:
![\begin{gathered} (w\circ u)(1)=\sqrt[]{1^2+15}=\sqrt[]{1^{}+15} \\ \\ (w\circ u)(1)=\sqrt[]{16} \\ \\ (w\circ u)(1)=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xds04w7a4rsg9t1w5t6pm1wyfzrrphh1cg.png)
Now we have the second answer: (w ∘ u)(1) = 4.